Allergy onset and local investor distraction - Pantzalis, Christos; Ucar, Erdem (Journal of Banking & Finance, 2018)
We posit that investor distraction can be exogenously triggered by allergy onset's degrading effects on local investors’ health and cognitive functioning. We document that allergy onset is related to lower trading activity. We use daily pollen counts to measure the severity of allergy onset at different locations and show that stocks of firms located in areas with severe allergy problems exhibit declines in trading volume and lower stock returns. Moreover, allergy onset is associated with both a decline in investor demand for firm information, as proxied by Google search volume, and stock underreaction to earnings news. Collectively our evidence supports the notion that the association of allergy onset and stock market outcomes may be emerging through a local investor distraction channel.